Character Education for Children in the Perspective of Hadith - Ahmad Khawani; Zulkipli Lessy; Junari Yulianti; Anjar Sulistiawati (IQRO: Journal of Islamic Education, 2022)
Character education constitutes putting essential values on students through a set of learning and valuable assistance in such a way that students are able to understand, experience, and integrate core values into their personality. At the same time, such education also embeds a character and promote values to preserve the distinct character when living the daily lives. Applying a model or notion of character does not guarantee that the students would be more creative immediately. However, actually they really need a fundamental concept for building of considerable character. To deal with it, Prophet Muhammad basically has developed a model of good character education in a hadith. This study is a library research with qualitative method. Data were collected by identifying related problems from books or articles through three steps: (1) data recording, (2) data combining, and (3) data analyzing to get the point and then converted into narratives in terms of character education according to the perspective of hadith. This educational model hopefully can change students’ behavior, attitude, and culture to create a civilized community.